Association between Knowledge of Sexually Transmitted Infections and Sources of the Previous Point of Care among Nigerians: Findings from Three National HIV and AIDS Reproductive Health Surveys - Morhason-Bello, Imran O.; Fagbamigbe, Adeniyi F. (International Journal of Reproductive Medicine, 2020)
Background. Adequate knowledge of sexually transmitted infections (STIs) is critical for effective control of disease. Health education/counselling at the point of care provides ample opportunities to improve knowledge of patient seeking treatment. There is no study from Nigeria that investigates association between sources of previous point of care of STI and quality of knowledge of people on STI. We hypothesised that previous treatment of STI will be associated with better knowledge of STI and HIV infection. Methods. Three consecutives nationally representative cross-sectional surveys on HIV and AIDS Reproductive Health in Nigeria, conducted in 2005, 2007, and 2012 were analysed. Outcome measures were knowledge of STI only, and a combined knowledge of STI and HIV transmission and prevention. We designed a knowledge scale of 14-item questions for STI and 41-item questions for STI and HIV. Logistic regression was used to identify risk factors at 5% significance level. Results. Knowledge of STI increased from 13.4% in 2005 to 15.0% in 2007 to 26.5% in 2012. Respondents that received treatment from pharmacy and patient medicine vendors had higher odds of good knowledge of STI than those who did not receive any treatment (aOR = 2.55) in 2005. In 2012, respondents treated at health facilities were over two times likely to have good knowledge of STI and HIV transmission and prevention (aOR = 2.35). STI positive individuals in the highest economic class were two times likely to have good knowledge of STI and HIV transmission and prevention than those in the lowest class. Conclusion. Participants that previously sought care from health facilities, pharmacy, and patient medicine vendors had better knowledge of STIs and HIV infection prevention and transmission than those who sought care from unorthodox sources. We recommend a national awareness creation on STI prevention including provision of information on safe point of care for STIs in Nigeria.